2003
DOI: 10.1091/mbc.e02-09-0562
|View full text |Cite
|
Sign up to set email alerts
|

A Dual Role of the GTPase Rac in Cardiac Differentiation of Stem Cells

Abstract: The function of the GTPase Rac1, a molecular switch transducing intracellular signals from growth factors, in differentiation of a specific cell type during early embryogenesis has not been investigated. To address the question, we used embryonic stem (ES) cells differentiated into cardiomyocytes, a model that faithfully recapitulates early stages of cardiogenesis. Overexpression in ES cells of a constitutively active Rac (RacV12) but not of an active mutant (RacL61D38), which does not activate the NADPH oxyda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 46 publications
1
47
0
2
Order By: Relevance
“…In this context, it is also important to point out that the regulation of ROS production by Rac1 is important for many cellular processes that are involved in signal transduction (129), actin cytoskeletal rearrangements (71,87,102), cell migration (143), cell proliferation (66,99,108,143), and cell differentiation (113). Given that many of these pathways also involve activation and recruitment of Rac1 to specific membrane domains, it is also possible that SOD1=Rac1 interactions may influence other cellular aspects of disease progression in ALS.…”
Section: The Sod1/rac1 Interaction Serves As a Redox-sensor For Redoxmentioning
confidence: 99%
“…In this context, it is also important to point out that the regulation of ROS production by Rac1 is important for many cellular processes that are involved in signal transduction (129), actin cytoskeletal rearrangements (71,87,102), cell migration (143), cell proliferation (66,99,108,143), and cell differentiation (113). Given that many of these pathways also involve activation and recruitment of Rac1 to specific membrane domains, it is also possible that SOD1=Rac1 interactions may influence other cellular aspects of disease progression in ALS.…”
Section: The Sod1/rac1 Interaction Serves As a Redox-sensor For Redoxmentioning
confidence: 99%
“…This led us to postulate that low doses of ROS are not detrimental but instead elicit dose-dependent biological responses. Indeed, excessive ROS levels repress the expression of several cardiac genes (Morel and Barouki, 1999;Puceat et al, 2003). For instance, Puceat et al (2003) reported that a daily treatment of EBs with H 2 O 2 prevented the beating activity in differentiating EBs.…”
mentioning
confidence: 99%
“…Indeed, excessive ROS levels repress the expression of several cardiac genes (Morel and Barouki, 1999;Puceat et al, 2003). For instance, Puceat et al (2003) reported that a daily treatment of EBs with H 2 O 2 prevented the beating activity in differentiating EBs. This is consistent with our observation that NOX4 overexpression in ESC leads to apoptosis (unpublished data).…”
mentioning
confidence: 99%
“…Similarly, overexpression of TBX5 (Fijnvandraat et al 2003a) and opioid peptide (Ventura and Maioli 2000) enhanced cardiomyogenic differentiation in embryonic carcinoma cells. Conversely, loss of beta-1 integrin (Fassler et al 1996) or alternatively overexpression of Rac-1 (Puceat et al 2003) decreased the levels of cardiomyogenesis in differentiating ES cells. Thus a large number of cytokines, inorganic molecules, and genes have been identified that influenced the ability of ES cells to generate cardiomyocytes.…”
Section: Identification Of Factors That Enhance Cardiomyogenic Differmentioning
confidence: 99%